Photoluminescence of erbium doped microcrystalline silicon thin films produced by reactive magnetron sputtering - Cerqueira, M. F. (2001)
Microcrystalline silicon thin films doped with erbium were produced by RF sputtering and their structural, chemical and optical properties were studied by X-ray diffractometry at grazing incidence, Rutherford back scattering and optical transmission spectroscopy. The samples exhibit a sharp photoluminescence (PL) spectrum from the Er centres with the strongest peak positioned at 1.536 microm with a full width at half maximum of about 8 nm. When the temperature varies between 5K and 300K the photoluminescence decreases only five fold, in contrast to the behaviour reported for monocrystalline silicon.